Advances in femtosecond laser micro-inscription and ablation of optical coherence tomography and optical coherence elastography phantoms - Smith, Graham N.; Kalli, Kyriacos; Withford, Michael (My University, 2013)
Optical coherence tomography is a method of optical signal acquisition and processing based upon interferometry, where scattering from the media of interest produces micrometer-resolution 3D images. Optical coherence elastography utilizes OCT to measure the local displacement of tissues under controlled applied load and the resulting strain on the material [1], producing 2D and 3D strain maps (elastograms). The technique can be used to image microscopic mechanical properties of tissue [2], through either quasi-static or dynamic loading regimes (<;10Hz or >10Hz respectively). Typically systems operate in the NIR, minimizing scattering and allowing for greater penetration depths. There are applications to conservation, diagnostic and interventional medicine facilitating detailed imaging at depths of several mm without sample preparation or the use of ionizing radiation, typical in ultrasound and MRI scans.
Keywords: Ultrafast optics; Phantoms; Biomedical optical imaging; Optical imaging; Coherence; Optical interferometry